2008
DOI: 10.1103/physrevb.78.081405
|View full text |Cite
|
Sign up to set email alerts
|

Efficient sticking of surface-passivated Si nanospheres via phase-transition plasticity

Abstract: Large-scale atomistic simulations considering a 5 nm in radius H-passivated Si nanosphere that impacts with relatively low energies onto a H-passivated Si substrate reveal a transition between two fundamental collision modes. At impacting speeds of less than ϳ1000 m / s particle-reflection dominates. At increased speeds the partial onset in the nanosphere of a ␤-tin phase on the approach followed by a-Si phase on the recoil is an efficient dissipative route that promotes particle capture. In spite of significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…Moreover, the process occurs in silicon, which melts at ∼1690 K, and where the range of collisional fusion speeds is ΔV c ∼ 100-1000 m s −1 , as seen in the recent molecular Vol. 719 dynamics simulations of Suri & Dumitricǎ (2008). Finally, bodies of inhomogenous composition can fuse in this manner.…”
Section: Overview Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the process occurs in silicon, which melts at ∼1690 K, and where the range of collisional fusion speeds is ΔV c ∼ 100-1000 m s −1 , as seen in the recent molecular Vol. 719 dynamics simulations of Suri & Dumitricǎ (2008). Finally, bodies of inhomogenous composition can fuse in this manner.…”
Section: Overview Of Resultsmentioning
confidence: 99%
“…The molecular dynamics simulations of Suri & Dumitricǎ (2008) provide an excellent example of damage-induced polyamorphism and fusion in Si which experimentally melts at ∼1690 K. They find that in high-speed and hence high-pressure collisions the β-tin phase forms in an interfacial region followed by picosecond annealing to the a-Si phase. While the particles in their study are sufficiently small that were they in the inner nebula they would be strongly coupled to the gas phase, their work demonstrates the basic effect of low-speed rebound (V c ∼ 900 m s −1 ) and high-speed (V c ∼ 1640 m s −1 ) damage-induced fusion.…”
Section: Liquidity Versus Structural Phase Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been demonstrated that hydrogen coated Si nanoparticles exhibit the weak attraction by H atoms on the surface. [34,35] We believe that our model captures the essence of such a system. For realistic simulations, we may need to carry out another simulation of the collision of H-passivated Si clusters by introducing suitable empirical potentials.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the instability of the spherical shape and the plastic deformation in a cluster cause the increase of the internal temperature of the cluster. [33,34] We numerically performed free flights of cluster by the use of C 1055 to check the time evolution of the internal temperature of the cluster. Figure 11(b) shows the time evolution of the temperature inside the cluster C 1055 after giving the translational speed V = 0.07 ǫ/m and the initial temperature T = 0.02ǫ.…”
Section: Discussionmentioning
confidence: 99%